ISLAMIC RELIGIOUS EDUCATION TEACHERS’ COMPETENCE: A PEDAGOGICAL CONTENT KNOWLEDGE PERSPECTIVE - Rima RJ Fatimah (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2022)
This study aims to analyze Islamic Religious Education (PAI) teachers’ competence from the perspective of Shulman’s Pedagogical Content Knowledge (PCK) in junior high school learning contexts. A qualitative approach with a case study design was employed at SMP Bhakti Mulya. Data were collected through classroom observations, in-depth interviews with teachers and the principal, and analysis of instructional documents. Data were analyzed interactively through data reduction, data display, and conclusion drawing, while triangulation techniques were applied to ensure validity. The findings indicate that the PAI teacher has fulfilled most PCK indicators, particularly in content mastery, curriculum understanding, and classroom management. The teacher is able to integrate Islamic subject matter with basic pedagogical strategies and relate it to students’ real-life contexts. However, the diversity of instructional representations and differentiated learning strategies requires further development to foster more dialogical and reflective learning. Supporting factors include relevant educational background, institutional support, and professional development programs, whereas limited instructional time and innovation constraints remain challenges. This study highlights the relevance of PCK as an analytical framework for enhancing PAI teachers’ professionalism and improving the quality of Islamic education.